2021
DOI: 10.1002/jgh3.12675
|View full text |Cite
|
Sign up to set email alerts
|

Balloon‐occluded retrograde transvenous obliteration for gastric varices improves hepatic functional reserve in long‐term follow‐up

Abstract: Background and Aim: Balloon-occluded retrograde transvenous obliteration (BRTO) has been widely adopted for the management of gastric fundal varices (GVs). There are a few reports that BRTO leads to the improvement of mid-term and long-term hepatic functional reserve (HFR). We retrospectively investigated the longterm effect on HFR and prognosis among patients who had undergone BRTO for GVs. Methods: This single-center, retrospective study included 57successful patients out of 60 patients who underwent BRTO fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…The encephalopathy was resolved or signi cantly reduced in all 35 patients evaluated in ve studies (3,8,9,21,22). Also, another study found that serum albumin levels in gastric varices patients improved considerably at three years following the BRTO procedure (23). In a study by Kumamoto et al analyzing the long-term effects of a large splenorenal shunt (SRS) on liver function and survival, patients have divided into three groups; patients with no gastrorenal shunt (the control group), patients with untreated gastrorenal shunt and patients with gastrorenal shunts treated with BRTO.…”
Section: Discussionmentioning
confidence: 88%
“…The encephalopathy was resolved or signi cantly reduced in all 35 patients evaluated in ve studies (3,8,9,21,22). Also, another study found that serum albumin levels in gastric varices patients improved considerably at three years following the BRTO procedure (23). In a study by Kumamoto et al analyzing the long-term effects of a large splenorenal shunt (SRS) on liver function and survival, patients have divided into three groups; patients with no gastrorenal shunt (the control group), patients with untreated gastrorenal shunt and patients with gastrorenal shunts treated with BRTO.…”
Section: Discussionmentioning
confidence: 88%
“… 19 BRTO has a favorable effect on long-term hepatic functional reserve. 20 Comparisons between BRTO and TIPS have always been controversial. A retrospective study by Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“… Waguri et al. 112 Retrospective 57 Liver function after B-RTO ALBI scores and Child-Pugh class significantly decreased 3 years after B-RTO. Ishikawa et al.…”
Section: Beyond Hcc: Application Of the Albi Score/grade In General H...mentioning
confidence: 99%
“… [108] , [109] , [110] , [111] Further, the improvement of liver function associated with balloon-occluded retrograde transvenous obliteration for gastric varices or administration of rifaximin to control hyperammonaemia have been analysed with the ALBI score. 112 , 113 …”
Section: Beyond Hcc: Application Of the Albi Score/grade In General H...mentioning
confidence: 99%
See 1 more Smart Citation